Uji Daya Kecambah Cabai Merah Pada Berbagai Ekstrak dan Konsentrasi Pupuk Kasgotchar dengan Metode Uji Diatas Kertas - Zubair, Wildan; Mufriah, Dini; Zulpansyah, Ichpan; Mayly, Syarifa (JURNAL AGROPLASMA, 2025)
The objective of this study is to determine the germination capacity of red chili peppers in various types and concentrations of Kasgotchar extract using a paper-based test method. This study used a 6 x 3 x 2 Factorial RAK design. The type of Kasgotchar extract is the first factor, with six types (K1 = Kasgotchar 1, K2 = Kasgotchar 2, K3 = Kasgotchar 3, K4 = Kasgotchar 4, K5 = Kasgotchar 5, K6 = Kasgotchar 6), and the second factor is the concentration of Kasgotchar extract, with three concentration levels (E1 = 5% Kasgotchar extract, E2 = 10% Kasgotchar extract, E3 = 15% Kasgotchar extract). The parameters observed in this germination process were the germination index and the germination potential, measured at seven and fourteen days after sowing. The results of study showed that the treatment with Kasgotchar extract type only significantly affected the germination index at seven and fourteen days after sowing, as well as the potential for germination at seven days. The Kasgotchar extract concentration treatment did not show any significant effect on the germination index and potential at all observation ages. Meanwhile, the interaction between the type of Kasgotchar extract and the concentration of Kasgotchar extract only had a significant effect on the germination potential at fourteen days of seedling age. The highest germination index and the germination potential were obtained by the treatment of Kasgotchar extract type 6 (2.39 and 0.88), the treatment with 5 % concentration of Kasgotchar extract (1.54 and 0.76), and the interaction treatment between Kasgotchar type 6 with 5% concentration of Kasgotchar extract (2.44 and 0.90).  Keywords: red chili, germination index, germination potential, kasgotchar, BSF